Different Perspective of Understanding between Indonesian and Malaysian in Communication Style - Harisa Dwi Oktira; Umar Mono; Alemina Br.Perangin-angin (Austronesian: Journal of Language Science & Literature, 2022)
Since many people have different cultural groups or cultural values sometimes causes misunderstandings. The research used descriptive qualitative which to investigate the different perspectives of both cultures such as the problem of misunderstanding of communication, the difference in communication styles and also to investigate the contrasting perspective in oral or written communication. The respondents of the research are Indonesian and Malaysian who took on social media YouTube. In collecting the data, the researchers used the observation with a video on YouTube and used diary notes to write the essential data of the research. The results shown that even though Malaysia and Indonesia are neighboring countries and these two countries almost have similar cultures, there are some different perspectives of understanding, especially in communication. Two aspects of communication became the issues of these two countries such as verbal communication and non-verbal communication. The different perspectives of communication style which classified into two aspects, namely verbal communication and non-verbal communication. The different perspective of verbal communication style occurs by using the words used or intonation to communicate or transfer the meaning. Meanwhile, the different perspectives of verbal communication style can be seen in the mannerism such as gestures or mimicking of people.